STUDI PERUBAHAN SUHU PERMUKAAN LAUT MENGGUNAKAN CITRA SATELIT TERRA MODIS - Harliyanti, Novi Ika; Sukojo, Bangun Muljo; Jaelani, Lalu Muhamad (Geoid, 2011)
Sea Surface Temperature (SST) is an important parameter used to determine the quality of water. Many factors could affect the up tide or low tide of SST in a waters. That factors could be observed by comparing the SST in a waters for certain period. Madura Strait which is the estuary for large and small rivers have a SST that changes every season. The pattern of SST changes can be observed by using multi-temporal image. In this study used Terra / MODIS satellite images with 1 km of spatial resolution, so as to provide information on the distribution pattern of SPL in the Madura Strait region. The value of SST obtained from image processing by Brown and Minnet(1999) algoritm. To obtain the temperature value is used bands of 20, 31, and 32 which must be converted into brightness temperature.To get this SST pattern used in image data of Terra / MODIS for six years, from 2005 until 2010. The SST pattern results are the monthly and annual patterns. The results of data processing in the month that same with the month of groundtruth showed that R2= 71.91%. It means that imagery data could showed groundtruth data about 71.91%. Results of data processing for six years showed that the monthly pattern, the highest SST occurred in October, which the results of image processing is 33.87°C. The annual pattern shows that each year varies. The factors that cause SST changes are sunlight intensity, rainfall, and wind.